EMOTIONAL INTELLIGENCE OF FUTURE PSYCHOLOGISTS AND PHYSICIANS: A COMPARATIVE ANALYSIS AND PROSPECTS FOR EMOTIONAL COMPETENCE DEVELOPMENT - Yevchenko, Iryna (PSYCHOLOGICAL JOURNAL, 2025)
The article presents the results of an empirical study on emotional intelligence (EI) among students of psychology and medical programs, aiming to identify the specific features and developmental patterns of emotional competence in future professionals within helping disciplines. The sample consisted of 142 participants aged 19–20: 80 psychology students (4th year, National Pedagogical Dragomanov University) and 62 medical students (3rd year, Bogomolets National Medical University, majors in Pediatrics and General Medicine). To assess emotional intelligence, the Hall EQ-test was applied, which enables a comprehensive evaluation of emotional awareness, empathy, emotion recognition, and regulation skills. The findings revealed that the overall level of emotional intelligence in both groups remains predominantly at a low or moderate level. However, comparative analysis demonstrated statistically significant differences in specific EI components. Medical students showed higher scores in empathy and the recognition of others’ emotions, which may be explained by the clinical nature of their professional training and the need for sensitivity to patients’ emotional states. In contrast, psychology students exhibited greater awareness of their own emotions and higher levels of internal reflection. The overall emotional intelligence of medical students was slightly higher than that of psychology students, approaching the threshold of statistical significance (p ≈ 0.05). These results highlight the importance of systematically developing emotional competence within the educational curricula of both disciplines, particularly regarding empathic listening, emotional self-regulation, and professional self-awareness. The obtained data provide a basis for further research on emotional intelligence as a determinant of psychological well-being, effective interpersonal communication, and professional adaptation in medical and psychological education contexts.